One Disease, but Different Names: Fuchs’ Superficial Marginal Keratitis and Terrien Marginal Degeneration - I. A. Riks; S. V. Trufanov; Yu. S. Astakhov; M. Ezugbaya; S. S. Papanyan; E. I. Akopov (Oftalʹmologiâ)
Terrien marginal degeneration and Fuchs’ superficial marginal keratitis are considered rare and slowly progressive corneal diseases with a bilateral lesion, unknown etiology, and have a number of similar clinical signs. Clinically, Terrien marginal degeneration is characterized by peripheral thinning, which appears at the  beginning of the disease usually in the upper half, but can also begin with the lower half of the cornea. In the case of Fuchs’ superficial marginal keratitis, biomicroscopic examination, at the initial stages of the disease’s development, in the lower and lower nasal segments, reveals peripheral corneal thinning. As a rule, in  both diseases, the lesions on the two eyes are asymmetric, but peripheral corneal thinning is the main pathological sign. Purpose. To determine the diagnostic criteria for Terrien disease and Fuchs’ marginal keratitis, to identify their similarities and differences. Patients and methods. For the period 2017–2020, 40 patients were examined; they were divided into 3 groups. 30 patients with Terrien marginal degeneration, 7 patients with Fuchs’ superficial marginal keratitis, 3 patients with signs of Terrien marginal degeneration in one eye and typical manifestations of Fuchs’ superficial marginal keratitis in the other eye. The following methods were used for diagnostics: confocal microscopy,  optical coherence tomography of the anterior segment, keratotopography. Results. A survey of 40 patients revealed many common clinical signs of two previously considered separate diseases. According to the literature, it is known that the main difference between these two diseases is the localization of corneal lesions. We found that different localization of the lesion in Terrien degeneration and  superficial marginal Fuchs keratitis is present in some patients and only in the initial stages of both diseases. Conclusions. Terrien’s degeneration and Fuchs’ superficial marginal keratitis may be different variants of clinical manifestations or different stages of progression of the same disease. Since the etiology of Terrien’s degeneration and Fuchs’ superficial marginal keratitis had not been established, it is recommended to follow the clinical course of the diseases during treatment.